Mothers’ Physical Activity in the New Millennium: A Systematic Review of the Literature (Baltic Journal of Sport and Health Sciences, 2020)
Background. Physical activity is essential for health, especially in an increasingly sedentary world. Being a parent involves responsibilities that could interfere with mothers’ physical activity. Research suggests that mothers are especially vulnerable to physical inactivity. Health promoters invest substantial effort in facilitating the physical activity of women with children.Methods. The scope of this systematic literature review is to synthesize research efforts on mothers’ physical activity and supporting interventions. Three databases were scrutinized in this review (Medline, Scopus, and PsycINFO). Articles published between 2000–2020 were selected in concordance with the Preferred Reporting Items for Systematic Reviews and Meta-analysis (PRISMA). Fifty-four eligible articles were included after screening 3708 articles.Results. The results suggest that mothers exhibit lower levels of physical activity than the recommended level for adults. Lack of time, focus on childcare, limited knowledge, and insufficient spousal support emerge as the primary barriers to physical activity in mothers with children. Interventions trying to overcome these barriers vary in methods, evaluations, and effectiveness. Positive changes in mothers’ physical activity may emerge if interventions focus on increasing self-efficacy, problem-solving, goal setting, and other cognitive factors.Conclusion. Future interventions integrating internet-based applications and involving spouses and/or partners might help mothers to increase their physical activity.Keywords: exercise, health behavior, motherhood, sedentary, women.